2013
DOI: 10.1021/jp401648y
|View full text |Cite
|
Sign up to set email alerts
|

Solid/Liquid Phase Diagram of the Ammonium Sulfate/Glutaric Acid/Water System

Abstract: We have studied the low temperature phase diagram and water activities of the ammonium sulfate/glutaric acid/water system using differential scanning calorimetry, infrared spectroscopy of thin films, and a new technique: differential scanning calorimetry-video microscopy. Using these techniques, we have determined that there is a temperature-dependent kinetic effect to the dissolution of glutaric acid in aqueous solution. We have mapped the solid/liquid ternary phase diagram, determined the water activities ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…We have studied five dicarboxylic acid/(NH 4 ) 2 SO 4 /H 2 O ternary systems in our lab: C 3 H 4 O 4 /(NH 4 ) 2 SO 4 /H 2 O, C 4 H 4 O 4 /(NH 4 ) 2 SO 4 /H 2 O, C 4 H 6 O 5 /(NH 4 ) 2 SO 4 /H 2 O, C 5 H 8 O 4 /(NH 4 ) 2 SO 4 /H 2 O, and C 4 H 6 O 4 /(NH 4 ) 2 SO 4 /H 2 O studied in this paper. Table summarizes some of the key physical properties that we measured in these systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have studied five dicarboxylic acid/(NH 4 ) 2 SO 4 /H 2 O ternary systems in our lab: C 3 H 4 O 4 /(NH 4 ) 2 SO 4 /H 2 O, C 4 H 4 O 4 /(NH 4 ) 2 SO 4 /H 2 O, C 4 H 6 O 5 /(NH 4 ) 2 SO 4 /H 2 O, C 5 H 8 O 4 /(NH 4 ) 2 SO 4 /H 2 O, and C 4 H 6 O 4 /(NH 4 ) 2 SO 4 /H 2 O studied in this paper. Table summarizes some of the key physical properties that we measured in these systems.…”
Section: Resultsmentioning
confidence: 99%
“…This is much lower than would be expected when comparing the affect of ammonium sulfate on solubility in the other dicarboxylic acid systems in Table 3. However, when one compares the corrected C 5 H 8 O 4 /H 2 O phase diagram 46 to those of the other dicarboxylic acids in water, 26,47 we observe that the solubility of glutaric acid in water is much more temperature-dependent than the other acids. As an example, if we compare malonic and glutaric acids, we observe that these two compounds have the same solubility (63.15 wt %) in water at 302.7 K. However, at 273 K, the solubility of glutaric acid has dropped to 25.5 wt %, while that of malonic acid has only decreased to 51.9 wt %.…”
mentioning
confidence: 87%
“…Additionally, phase equilibrium has a considerable basic groundwork in the metal smelting process, fractional crystallization, semiconductors, ceramics, salt separation, and purification in natural ores. , The construction of ternary equilibrium phase diagrams is at the basis of these applications. Thermal analysis is a very useful practical method for studying phase diagrams, and calorimetric methods have been an invaluable tool for understanding the rich phase behaviors either in the early stages of process development or in phase equilibrium applications. Isothermal titration microcalorimetry (ITC) and reaction calorimetry are widely used calorimetric techniques alongside differential scanning calorimetry.…”
Section: Introductionmentioning
confidence: 99%
“…Given the abundance and importance of organic acids in atmospheric aerosols, measurements and models of thermodynamic properties of the organic species in solution are essential for accurate predictions of the gas/particle partitioning and aerosol size distribution and composition . Experimental thermodynamic studies include investigations into vapor pressure measurements and hygroscopic properties. Soonsin et al reported that organic acids with an even number of carbon molecules (“even acids”, e.g., succinic acid) are less soluble in water and have lower vapor pressures than odd acids. In a study of growth factor of hygroscopic acids such as malonic acid, citric acid, and malic acid, Peng et al found that these water-soluble organic acids at low concentrations contribute less than inorganics to the hygroscopicity of atmospheric aerosols.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of growth factor of hygroscopic acids such as malonic acid, citric acid, and malic acid, Peng et al found that these water-soluble organic acids at low concentrations contribute less than inorganics to the hygroscopicity of atmospheric aerosols. Extended to ternary systems, Beyer et al and Pearson and Beyer studied thermodynamic properties of dicarboxylic acids/ammonium sulfate/water mixtures using differential scanning calorimetry and infrared spectroscopy of thin films. They have reported water activities and solid/liquid ternary phase diagrams for systems having dicarboxylic acids like malonic, glutaric, maleic, and succinic acids below 300 K. Bilde et al have reviewed experimental measurements of equilibrium vapor pressures from evaporation rate of straight-chain dicarboxylic acids with water and inorganics.…”
Section: Introductionmentioning
confidence: 99%